Incoming flow calculation in Nam Theun 2 Reservoir - PHONGSA, Daovy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Laos is a country with a humid tropical climate, consisting of two seasons: the rainy season and the dry season. The southwest monsoon influences the region from mid-May to early October, while the northeast monsoon affects the area from early November to mid-March. Generally, the average annual rainfall ranges from 1400 mm to 2500 mm and exceeds 3500 mm in the central and southern regions. In September 2018, a hydroelectric dam encountered issues, causing part of the dam to collapse in southern Laos, Attapeu province. This disaster resulted in severe damage, with 98 people missing and 6,600 people displaced. In early September 2024, northern Laos experienced sudden flooding in Luang Namtha province, causing significant property damage. Additionally, heavy rainfall influenced by Typhoon Yagi led to the release of water from northern Laos dams for safety, including Nam Tha, Nam Ou, Nam Lik, Nam Khan 2-3, and Xayaburi dams. The issues arose from heavy rainfall and miscalculations in water flow into reservoirs, particularly in dam water management to provide early warning information to downstream communities. The purpose of this study is to assess the accuracy of the Intergrade Flood Analysis System (IFAS) model in calculating water inflow into reservoirs, specifically Nam Theun 2, to support to the water management and prevent flood-related issues. The performance of the IFAS model result used NSE (Nash-Sutcliffe efficiency), PBIAS (percent bias), R2 (coefficient of determination), and RSR (root mean square error) to compare calculated by IFAS and the water balance from 2010 to 2024, with results of NSE = 0.58, PBIAS = 8.79, R2 = 0.68, and RSR = 0.65. The 2023 study showed the highest accuracy with NSE = 0.73, PBIAS = -12, R2 = 0.83, and RSR = 0.52, Ev = 9.6 % The findings concluded that the IFAS model can calculate daily water inflow but has limitations in calculating peak and the extreme climate dry condition, such as in 2020 and 2022.